Infância e desigualdades no Brasil: uma reflexão a partir dos relatos da publicação Eu, empregada doméstica de Preta-Rara - Ana Julieta Teodoro Cleaver (IdeAs)
Rapper, history teacher, and former domestic worker, Preta-Rara shared her experience of domestic work on social media in 2016 and invited her readers to share their stories, marking the hashtag "euempregadadomestica" (in English, "Idomesticworker"). She received thousands of stories, which tell the reality lived by more than 5 million domestic workers in Brazil. The commitment generated by Preta-Rara’s call nevertheless reveals a profession that is often invisibilized. A compilation of these stories was the object of a publication. This article aims to analyze child domestic work in Brazil, in the light of the stories published by Preta-Rara. Indeed, the analysis of child domestic work makes it possible to address Brazilian historical inequalities and the intersectionality inherent in the category. The stories compiled by Preta-Rara serve as a guideline for discussing childhood and inequalities in Brazil, specifically the issues related to girls employed as domestic workers.